2006
DOI: 10.1111/j.1468-0297.2006.01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Educational Tracking Affect Performance and Inequality? Differences‐ in‐Differences Evidence Across Countries

Abstract: Even though some countries track students into differing-ability schools by age 10, others keep their entire secondary-school system comprehensive. To estimate the effects of such institutional differences in the face of country heterogeneity, we employ an international differencesin-differences approach. We identify tracking effects by comparing differences in outcome between primary and secondary school across tracked and non-tracked systems. Six international student assessments provide eight pairs of achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
566
5
28

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 834 publications
(625 citation statements)
references
References 22 publications
26
566
5
28
Order By: Relevance
“…The results of these studies are congruent (see Gorard & Smith, 2004;Hanushek & Woessmann, 2006;Mons, 2007;Dupriez et al, 2008;Monseur & Crahay, 2008), and there is a broad consensus among researchers. School systems with early tracking (characterised by significant differences of composition between schools, as in Germany, Austria, Belgium, Hungary, Switzerland and the Czech Republic) increase differences in performances between students and are, moreover, less equitable.…”
Section: Impact Of the Institutional Contextsupporting
confidence: 62%
See 1 more Smart Citation
“…The results of these studies are congruent (see Gorard & Smith, 2004;Hanushek & Woessmann, 2006;Mons, 2007;Dupriez et al, 2008;Monseur & Crahay, 2008), and there is a broad consensus among researchers. School systems with early tracking (characterised by significant differences of composition between schools, as in Germany, Austria, Belgium, Hungary, Switzerland and the Czech Republic) increase differences in performances between students and are, moreover, less equitable.…”
Section: Impact Of the Institutional Contextsupporting
confidence: 62%
“…In the section titled 'Impact of the Institutional Context', we mentioned (e.g. Hanushek & Woessmann, 2006) a well-known finding: early tracking is nearly always linked with increased social inequality in academic performance. Young people from underprivileged backgrounds more often attend less prestigious tracks.…”
Section: Discussionmentioning
confidence: 99%
“…Hanushek and Woessmann (2006) compare the performance of fourth graders, i.e. prior to tracking, with the performance of eighth or ninth graders, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, the existing crude system of streaming does not benefit struggling students. In fact, research has shown that early tracking/streaming may decrease achievement of all students and also increase educational inequality, by leading to a greater reduction in achievement for low-achieving students than high-achieving students (Hanushek & Wobmann, 2006). To the extent that the early achievement gap is associated with differences in family background, track placements may reflect these differences and lead to further disparities in education.…”
mentioning
confidence: 99%